The objective subject: John Broadus Watson, behaviourism, and the progressive era in twentieth-century america, 1900–1950s - Ng, Ping Siang (Nanyang Technological University, 2024)
To date, the discipline of psychology is noted to be a study of mind and behaviour by the American Psychological Association. Yet, almost a century ago, “behaviour” as a tool in studying the human psyche was met with fierce opposition and critique by mainstream American psychologists then. Behaviour was a tool of comparative psychologists who operated on animals and was deemed by introspective psychologists to be superficial in human psychology. Yet, the advent of the twentieth century saw the rise of behaviourism in both academic and advertising circles despite behaviourism hardly making a dent within mainstream psychology in the decades prior. By conducting a biographical analysis of John Broadus Watson’s life, this paper investigates how social factors both produced and legitimised what constituted as “truth” in early-twentieth century American psychology. It reveals how Progressive ideals and beliefs about the role scientific dressmaking could play in American society allowed for the reversal of the power dynamics between behaviourism and introspection. In addition, the paper explores how behaviourism, despite claiming to be objective in both principle and methodology, was ultimately constructed by Watson’s social opinions as well as “authenticated” by the various non-academic entities that desired an “objective” and “stable” way to control humans.